Implikasi Pagelaran TariBarong dan Keris Terhadap Sosial Ekonomi Sekaa Pagelaran Tari Barong dan Keris di Pura Puseh Desa Batubulan, Kecamatan Sukawati, Kabupaten Gianyar - Saputra, I Putu Risky; Pujani, Luh Putu Kerti (JURNAL DESTINASI PARIWISATA; Vol 9 No 2 (2021): VOL 9, NO 2 (2021): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2021.v09.i02.p23, 2021)
Barong and Keris Dance performances at Puseh Temple in Batubulan Village hasvarious implications for the socio-economic aspects of sekaa Barong and Keris Dance performance. This study aims to determine the implications of the Barong and Keris Dance performances at Puseh Temple in the Batubulan Village. There is a main concept used, namely the socio-economic concept. The type of data in this study uses qualitative data sourced from primary data and secondary data. Data collection techniques are by observation, interviews, and documentation. The data analysis technique in this study used qualitative analysis techniques. The results of this study are the implications of Barong and Keris Dance performances on the socio-economic sekaa of Barong and Keris Dance performance at Puseh Temple in Batubulan Village, namely, the implications that create job opportunities in Barong and Keris Dance performances, implications for the income of sekaa of Barong and Keris Dance performances, and implications for welfare sekaa Barong and Keris Dance performances at Puseh Temple in Batubulan Village, Sukawati District, Gianyar Regency. Keywords : Implications, Socio-Economic, Barong and Keris Dance.